Impact of underlying plaque type on strut coverage in the early phase after drug-eluting stent implantation. Issue 8 (December 2018) - Kakizaki, Ryota; Minami, Yoshiyasu; Hashikata, Takehiro; Nemoto, Teruyoshi; Hashimoto, Takuya; Fujiyoshi, Kazuhiro; Meguro, Kentaro; Shimohama, Takao; Tojo, Taiki; Ako, Junya
Abstract : Background: The aim of this study was to investigate whether the underlying plaque type affects the neointimal coverage after drug-eluting stent implantation. Methods: A total of 1793 struts in 22 zotarolimus-eluting stents were assessed using optical coherence tomography imaging within 3 months of implantation. Neointimal coverage was evaluated within 5 mm from each stent edge on cross-sectional optical coherence tomography images at every 1-mm interval. The percentage of struts covered by neointima was compared among the normal segment group, the fibrous plaque group, and the lipid plaque group on the basis of the underlying plaque type. Results: The percentage of covered strut was significantly lower in the normal segment group than in the fibrous plaque group (35.9±30.2 vs. 57.1±31.0%, P <0.05) and the lipid plaque group (vs. 64.7±23.5%, P <0.01). The neointima was significantly thinner in the normal segment group than in the lipid plaque group (19.0±22.3 vs. 32.0±18.8 μm, P <0.01). The percentage of struts on the normal segment was significantly higher in cross-sections with a ratio of uncovered to total struts per section more than 0.3 than in cross-sections with a ratio up to 0.3 (32.4±31.7 vs. 19.5±33.8%, P <0.01). Conclusion: Struts on the normal segment were less covered and had thinner neointima than struts on the lipid plaque at the stent edge within 3 months after zotarolimus-eluting stent implantation. Caution should be exercised when implanting longer drug-eluting stents to achieve uniform strut coverage in the early phase. Abstract : Supplemental Digital Content is available in the text.